Analysis of Thermo-Optic Tunable Dispersion-Engineered Short-Wavelength-Pass Tapered-Fiber Filters - Chou, Sen-Yih; Hsu, Kuei-Chu; Chen, Nan-Kuang; Liaw, Shien-Kuei; Chih, Yu-Syun; Lai, Yinchieh; Chi, Sien (My University, 2009)
Thermo-optic tunable short-wavelength-pass tapered-fiber filters based on fundamental-mode cutoff mechanism are realized experimentally and analyzed theoretically. The effects of material and waveguide dispersion are investigated and the optimal tapered fiber structures for attaining high-spectral cutoff slope and high-rejection efficiency are determined.
Keywords: Dispersion engineering; fiber filters; fiber optics; fiber tapering; fundamental-mode cutoff; thermo-optic